Organizational Strengthening of Forum Bela Negara DKI Jakarta through Event Management - Intan Putri Cahyani; Wahidah R. Bulan; Windhiadi Yoga Sembada (MITRA: Jurnal Pemberdayaan Masyarakat, 2020)
According to Law No. 3 of 2002 on National Defense, the defense of the State is the responsibility of all citizens of Indonesia, including community organizations. Forum Bela Negara (FBN) DKI Jakarta, a community organization formed with the specific purpose of overseeing efforts to strengthen the values of the country's defense in society, has long been taking part in implementing the law. FBN, especially in the DKI Jakarta province, has organized many activities such as regular, comprehensive, and integrative socialization of fostering awareness of defending the country to the cadres and the public, as well as supporting and carrying out government programs for the creation of the National Defense Cadre. This is in line with the Presidential Instruction (Inpres) No. 7 of 2018 concerning the 2018-2019 National Action Plan of Nation Defense, which states that the internalization of the basic values of state defense to the general public is one of the intended action plans. The problems faced by FBN DKI Jakarta include the measurability of the results of activities and the ineffectiveness of the approach (model) of activities that have been held. The voluntary nature of membership in mass organizations (Law No.17 of 2013 article 1 paragraph 1) has caused FBN to have many limitations including in Event Management. The purpose of this community service program was to strengthen the FBN's institutions by increasing the soft skills and hard skills of the DKI Jakarta FBN Management on Event Management, which included, among others, the approach of implementing activities, making creative proposals, and raising funds. The method used in this program was as follows. First, a need assessment was conducted; next, a mini-workshop on Event Management was held, and finally, a Coaching Clinic or supervision to the idea of DKI Jakarta FBN activities was provided. Institutional strengthening was chosen because FBN as a mass organization has a strategic function in carrying out social change, such as supporting efforts to instill nationalism spirit and awareness of the defense of the people's state. The output of this activity was, among others, increasing knowledge and skills of the DKI Jakarta FBN Management related to Event Management, as evidenced by the draft proposal they had prepared. The core of this activity was to identify an adaptive, contemporary approach ranging from planning, implementation, and an evaluation in the activities carried out by the State Defense Forum.